First record of Oligochoerus limnophilus (Acoela, Acoelomorpha) from British waters - M. Vila-Farré; M. Álvarez-Presas; J. G. Achatz (Arxius de Miscel-lània Zoològica)
We report the occurrence of the acoel Oligochoerus limnophilus (Acoelomorpha) from the British Islands, based on specimens captured in the river Thames (locally known as the river Isis) in Oxford, England, thereby considerably widening the distributional range of the species that had formerly been reported only from continental Europe. We further present live images and CLSM-projections of systematically informative structures that corroborate a close relationship with the genus Convoluta Ørsted, 1843.